Morbidity and treatment-seeking pattern among low birth weight infants: A community-based cohort study from Puducherry - Sreeja Manghat; Sonali Sarkar; Sitanshu Sekhar Kar; Adhisivam Bethou (Wolters Kluwer Medknow Publications, 2024)
Background: To compare the morbidity and treatment-seeking pattern of low birth weight (LBW) and normal birth weight (NBW) infants during the first six months. Material and Methods: A prospective cohort study was conducted in the service areas of eight urban primary health centers of Puducherry from October 2019 to July 2021. Details of LBW and sex-matched NBW infants were obtained from the birth registers of selected PHCs. Data were collected using a structured interview schedule on completion of the first, third, and sixth months at their homes. For comparison, Mid-p exact test was used for incidence rates, t-test/Mann-Whitney for continuous variables and the Chi-square/Fisher's exact test for the categorical variables. Results: Ninety-four pairs of LBWS and NBW infants were recruited. The incidence of morbidity during the first six months among LBW and NBW infants was 37.5 and 33.3 episodes per 100 child months, respectively (P value 0.118). Though the incidence of all-cause morbidity was similar, skin infections were significantly higher among LBW (3.10 vs 1.21 per 100 child months, P = 0.04). The incidence of all-cause morbidity was high in LBW infants with poor weight gain. Conclusion: Birth weight was associated with all-cause morbidity during the first three months. However, this association varied in age points and infants' weight gain.